“THE STRENGTH” OF TERRITORIAL AUTONOMY AND LANGUAGE PREFERENTIAL POLICY IN CONTEMPORARY WORLD - Nadezhda V. Borisova (Сравнительная политика, 2018)
A language is one of the signifi cant factors that determine the structural characteristics of ethnic territorial autonomies. At the same time it is the object of preferential language policy that conducted by both national and regional governments. The article focuses on the question about the interrelation between the strength of autonomy and the scope of language preferential policy institutionalization. Last one is manifested in the weight of linguistic territorial regime. As a result of correlation analysis (the sample includes 28 cases) and comparative-oriented case-study analysis of Wales and Scotland in UK, Basque Country in Spain and Vojvodina in Serbia the structural and contextual factors causing or violating links between the strength of autonomy and the scope of language preferential policy institutionalization were identifi ed. The features of the community’ ethnic structure and ethno-linguistic minority share are the structural factors. The size of minority share affects the strategy and resources of the political actors who able to manifest language requirements and to convert it into institutionalized language policy. These actors are political parties, ethnic councils and NGO. The historical background and political context of ethnic territorial autonomy formation and language preferential policy institutionalization constitute the second group of factors. The logic of interrelation of both groups of factors is explained.